Development of Nutritional Education Media for Fruit and Vegetable Snakes Based on Adobe Flash Cs6 for Primary School Children - Andini, Ni Made Putria Mutia; Emilia, Esi; Ampera, Dina; Mutiara, Erli; Juliarti, Juliarti (Universitas Pendidikan Indonesia (UPI), 2024)
Lack of nutrition education media related to the benefits of fruits and vegetables for elementary school children so that knowledge related to fruits and vegetables is still lacking. One of the efforts that can be done is to create a nutrition education media. This study aims to develop educational media for snake ladder nutrition based on Adobe Flash CS6 to increase nutritional knowledge about fruits and vegetables in elementary school children and to determine the feasibility of nutrition education media for snake ladder fruit and vegetables based on adobe flash CS6 for elementary school children. This research is an R D research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) conducted at SDN 104196 Tandam Hulu II. The sample in this study was a sample of the validity of the material and media, namely lecturers and teachers, totaling 3 people, and a trial sample containing 5 people, as well as a large group trial sample consisting of 28 people. The results of the validity test carried out by media experts were 93 with 93% eligibility and the category was very feasible. The results of the validity test conducted by two material experts were 94% and 96% with a very feasible category. And the results of the feasibility test of students with the eligibility category of 90.22% with the appropriate category.